Pollen development and morphology in four species of pterocactus (Cactaceae) - Gotelli, Marina María (2009)
We report a detailed study of the development and morphology of pollen in four species of the genus Pterocactus (Cactaceae), carried out by using LM and SEM. The anther is tetrasporangiate, its wall consists of epidermis, endothecium, one middle layer and a binucleate secretory tapetům. Microspore tetrads are tetrahedrical and pollen grains are shed at bicellular stage. Pollen grains are pantoporate, with a perforate tectum and supratectate spinules.